Edukasi Pola Hidup Sehat dan Penguatan Spiritual Keluarga dalam Menyambut Bulan Suci Ramadhan di Desa Amola Kecamatan Binuang Kabupaten Polewali Mandar - Irwani Lisaw; Jumriani Jumriani; Jumadi Madi; Sitti Nurmadia; Mardia Mardia; Yeyen Tumena; Muhammad Aswar; Nadira Wulandari; Hasna Hasna; Siti Ria; Dian Dian; Qiran Askar; Rahmawati Rahmawati; Bidin Ma’ruf; Arsal Arsal (FKIP Universitas Mataram, 2026)
This community service program aimed to improve the knowledge, attitudes, and practical skills of the residents of Amola Village, Binuang District, Polewali Mandar Regency, in adopting healthy lifestyle practices while strengthening their mental and spiritual preparedness for the holy month of Ramadan. The program employed lectures, interactive discussions, and mentoring sessions integrated into Islamic educational activities held at the Grand Mosque of Amola Village. Participants included village government officials, community leaders, religious leaders, housewives, and members of local Majelis Taklim (Islamic study groups). Program effectiveness was evaluated using pre-test and post-test assessments to measure participants' understanding before and after the activities. The findings indicated significant improvements across all measured dimensions. The average knowledge level increased from 42.9% to 92.9%, attitudes improved from 54.7% to 96.4%, and practical skills increased from 39.3% to 86.9%. Participants also demonstrated a better understanding of healthy dietary management during fasting and greater spiritual awareness, reflected in their stronger commitment to improving the quality of worship, fostering family harmony, and strengthening social solidarity. In conclusion, integrating health education with Islamic values proved effective in enhancing the physical, mental, and spiritual preparedness of the community for observing Ramadan.